(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Brands yearn to decode customer whispers and shouts on the bustling streets of Twitter. Sentiment analysis acts as a magic decoder ring, unlocking the emotions behind every tweet. This powerful tool reveals areas of delight, discontent, and apathy, guiding brands towards data-driven decisions. It’s a swift shield against online storms, helping brands steer clear of negativity and amplify positive buzz. Embrace the whispers, understand the roar, and watch your brand soar.